2019
DOI: 10.1038/s41564-019-0364-2
|View full text |Cite
|
Sign up to set email alerts
|

Expanding anaerobic alkane metabolism in the domain of Archaea

Abstract: Methanogenesis and anaerobic methane oxidation through methyl-coenzyme M reductase (MCR) as a key enzyme have been suggested to be basal pathways of archaea 1 . How widespread MCR-based alkane metabolism is among archaea, where it occurs and how it evolved remain elusive. Here, we performed a global survey of MCR-encoding genomes based on metagenomic data from various environments. Eleven high-quality mcr-containing metagenomic-assembled genomes were obtained belonging to the Archaeoglobi in the Euryarchaeota,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
226
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 161 publications
(244 citation statements)
references
References 53 publications
17
226
1
Order By: Relevance
“…Newly assembled Archaeoglobi MAGs, including MAGs of "Ca. Polytropus marinifundus" (Juan de Fuca Ridge, Northeast Pacific Ocean), Archaeoglobi WYZ-LMO1 (Washburn Spring, WY, USA), WYZ-LMO2 (Obsidian Pool, WY, USA), and WYZ-LMO3 (Obsidian Pool, WY, USA), were retrieved from previous studies (7,17).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Newly assembled Archaeoglobi MAGs, including MAGs of "Ca. Polytropus marinifundus" (Juan de Fuca Ridge, Northeast Pacific Ocean), Archaeoglobi WYZ-LMO1 (Washburn Spring, WY, USA), WYZ-LMO2 (Obsidian Pool, WY, USA), and WYZ-LMO3 (Obsidian Pool, WY, USA), were retrieved from previous studies (7,17).…”
Section: Methodsmentioning
confidence: 99%
“…1; see also Fig. 2A and C), were downloaded from the NCBI database and included into this study (7).…”
Section: Anme-2dmentioning
confidence: 99%
“…In particular, it has been found that archaea are functionally diverse, being capable of ammonia oxidation, methane metabolism, and organic matter degradation [6][7][8]. Novel archaeal phyla with unusual metabolic potentials are still being discovered, for example, Nezhaarchaeota and Helarchaeota, two new archaeal phyla identified in 2019, were found to possess the potential for anaerobic short-chain hydrocarbon cycling [9,10]. In contrast to the increasing knowledge gleaned from archaeal community composition and metabolic capacity characterization, much less is known about the spatiotemporal dynamics of archaeal community distribution, their assembly mechanism, and inter taxa association in sediments [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the recently described process of multi-carbon alkane oxidation by archaea co-occurs with anaerobic methane oxidation by ANME archaea. Previous observations of these phenomena have mainly featured hydrothermal vent environments 15, 22, 38 whereas this deep sea setting experiences permanently low temperatures. Methane oxidizers are most abundant, in agreement with the high concentration of methane; however, by investigating an environment that also has relatively high concentrations of C 2+ gases, the potential and importance of both GoM-Arc1- and Syntrophoarchaeaum - like archaea degrading thermogenic hydrocarbons in cold seep sediments is shown for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have focused on anaerobic oxidation of methane, since methane generally is the dominant hydrocarbon in cold seep fluids. This process is mediated by anaerobic methanotrophic archaea (ANME) through the reverse methanogenesis pathway, typically in syntrophy with bacteria that can reduce electron acceptors such as sulfate, nitrate, and metal oxides 8, 15, 16 . Investigations of enrichment cultures have also revealed anaerobic bacterial or archaeal oxidation of non-methane alkanes and aromatic hydrocarbons, including ethane (e.g.…”
Section: Introductionmentioning
confidence: 99%